The Impact of the Business Environment on Young Firm Financing - Chavis, Larry W.; Klapper, Leora F.; Love, Inessa (World Bank, 2013)
A unique dataset of over 70,000 firms, most of which are small, in over 100 countries, is utilized to systematically study the use of different financing sources for new and young firms. Consistent age-related patterns emerge. Across all countries younger firms rely less on bank financing and more on informal financing. There is a clear substitution effect: as firms mature, more firms switch out of informal finance toward bank finance, while the total proportion of firms using external finance remains relatively unchanged. Importantly, these relationships hold for firms of different sizes, firms in different sectors, and firms located in countries with different income levels and on different continents. Thus, these patterns of young firm financing show clear universal tendencies. Given that even small firms increasingly use formal bank financing over time, these results suggest that information asymmetry plays an important role in decreasing a young firm's ability to obtain bank finance.